Comparison of tenecteplase with alteplase for the early treatment of ischaemic stroke in the Melbourne Mobile Stroke Unit (TASTE-A): a phase 2, randomised, open-label trial. Issue 6 (June 2022) - Bivard, Andrew; Zhao, Henry; Churilov, Leonid; Campbell, Bruce C V; Coote, Skye; Yassi, Nawaf; Yan, Bernard; Valente, Michael; Sharobeam, Angelos; Balabanski, Anna H; Dos Santos, Angela; Ng, Jo Lyn; et al.
Summary: Background: Mobile stroke units (MSUs) equipped with a CT scanner reduce time to thrombolytic treatment and improve patient outcomes. We tested the hypothesis that tenecteplase administered in an MSU would result in superior reperfusion at hospital arrival, when compared with alteplase. Methods: The TASTE-A trial is a phase 2, randomised, open-label trial at the Melbourne MSU and five tertiary hospitals in Melbourne, VIC, Australia. Patients (aged ≥18 years) with ischaemic stroke who were eligible for thrombolytic treatment were randomly allocated in the MSU to receive, within 4·5 h of symptom onset, either standard-of-care alteplase (0·9 mg/kg [maximum 90 mg], administered intravenously with 10% as a bolus over 1 min and 90% as an infusion over 1 h), or the investigational product tenecteplase (0·25 mg/kg [maximum 25 mg], administered as an intravenous bolus over 10 s), before being transported to hospital for ongoing care. The primary outcome was the volume of the perfusion lesion on arrival at hospital, assessed by CT-perfusion imaging. Secondary safety outcomes were modified Rankin Scale (mRS) score of 5 or 6 at 90 days, symptomatic intracerebral haemorrhage and any haemorrhage within 36 h, and death at 90 days. Assessors were masked to treatment allocation. Analysis was by intention-to-treat. The trial was registered with ClinicalTrials.gov, NCT04071613, and is completed. Findings: Between June 20, 2019, and Nov 16, 2021, 104 patients were enrolled and randomly allocated to receive either tenecteplase (n=55) or alteplase (n=49). The median age of patients was 73 years (IQR 61–83), and the median NIHSS at baseline was 8 (5–14). On arrival at the hospital, the perfusion lesion volume was significantly smaller with tenecteplase (median 12 mL [IQR 3–28]) than with alteplase (35 mL [18–76]; adjusted incidence rate ratio 0·55, 95% CI 0·37–0·81; p=0·0030). At 90 days, an mRS of 5 or 6 was reported in eight (15%) patients allocated to tenecteplase and ten (20%) patients allocated to alteplase (adjusted odds ratio [aOR] 0·70, 95% CI 0·23–2·16; p=0·54). Five (9%) patients allocated to tenecteplase and five (10%) patients allocated to alteplase died from any cause at 90 days (aOR 1·12, 95% CI 0·26–4·90; p=0·88). No cases of symptomatic intracerebral haemorrhage were reported within 36 h with either treatment. Up to day 90, 13 serious adverse events were noted: five (5%) in patients treated with tenecteplase, and eight (8%) in patients treated with alteplase. Interpretation: Treatment with tenecteplase on the MSU in Melbourne resulted in a superior rate of early reperfusion compared with alteplase, and no safety concerns were noted. This trial provides evidence to support the use of tenecteplase and MSUs in an optimal model of stroke care. Funding: Melbourne Academic Centre for Health.